"CHANCIFY" PWA (Progressive Web App) Learning Application to Enhance Motivation and Support Critical Thinking Skills - Fasha, Eka Farida; Hafiz Multazam Azhar; Khurotul Aeni (Integral (Jurnal Penelitian Pendidikan Matematika), 2024)
Abstract The development of technology in the 21st century has brought significant changes across various sectors, including education. Education must continuously adapt to remain relevant by leveraging technology, such as developing technology-based learning applications. The "Chancify" PWA (Progressive Web App) was developed to enhance student learning motivation and support students' critical thinking skills. This application provides comprehensive materials, practice questions, quick calculation features, interactive quizzes, and a chat feature to support learning. This research used a development research method, which included stages of preliminary study, planning, validation, final product review, and dissemination. Validation results showed that the application is valid with a score of 84.72% from media experts and 92.5% from subject matter experts. The practicality of the application was rated at 82.75% by users, indicating that the application is practical and valid. Motivation survey results showed a significant increase in students' learning motivation. The findings of this study are expected to improve the quality of education and student achievement.